Pengaruh Model Pembelajaran Contextual Teaching and Lerning (CTL) Materi Laju reaksi: Literature Review terhadap Kemampuan Berfikir Kritis dan Karakter Siswa - Muh. Arwin; Masrid Pikoli; Mangara Sihaloho; Wiwin Rewini Kunusa; Julhim S. tangio; Haris Munandar (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study focuses on the effect of applying the Contextual Teaching and Learning (CTL) model in the topic of reaction rate on the ability to think critically and the formation of character values of students in geographically remote areas (remote areas). This approach is designed to strengthen learners' understanding of scientific concepts in a relevant and contextual manner, by connecting them to the dynamics of real life - both in the personal, social and cultural domains. Thus, learners have the opportunity to build conceptual insights and adaptive skills independently. In addition, this real situation-based method contributes to fostering character values such as responsibility, discipline, innovation, curiosity, as well as social interaction skills and effective communication during the learning process. The literature review was conducted by collecting scientific publications released between 2018 and 2025. The findings of this review confirmed that the CTL approach has a real positive impact in honing critical thinking skills and fostering learners' character that supports their academic achievement. Therefore, it can be concluded that CTL is an efficient and relevant pedagogical method to be applied in teaching high school chemistry.